INCREASING STUDENTS’ VOCABULARY USING JUMBLED SENTENCES: ACTION STUDY RESEARCH - Melisa Octaviana; Hafizhatu Nadia; Tenny Murtiningsih (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to increase students' English vocabulary by using Jumbled Sentences in a small classroom. The subjects of this study were composed of seven students. This study used Classroom Action Research (CAR) as the method and was conducted by collaboration between teacher and researcher. The data were gathered through observation, interviews, field notes, and tests. The result of the study showed there was an improvement in student abilities. Student scores have increased significantly. In the first cycle post-test, only one out of seven students got good grades, with the Kriteria Ketuntasan Minimum (KKM) of English lessons being (75). Meanwhile, the student's scores in the second cycle post-test showed that seven of seven students scored above 75. In addition, there was a positive response from the English teacher and students about this study. In conclusion, jumbled sentences could increase students' abilities, especially in their vocabulary